Recycling and reclamation of asphalt pavements using in-place methods - Stroup-Gardiner, Mary, 1953- (Transportation Research Board, 2011)
"Discusses the use of hot in-place recycling, cold in-place recycling, and full-depth reclamation of asphalt pavements. In-place recycling and reclamation of asphalt pavements provides agencies with the ability to optimize the value of in-place materials, minimize construction time and traffic flow disruptions, and reduce the number of construction vehicles moving in and out of the construction area."--Provided by publisher.
At head of title: National Cooperative Highway Research Program.
"A synthesis of highway practice."
Keywords: Pavements, Asphalt -- Recycling.; Pavements, Asphalt -- Maintenance and repair.; elektronické knihy; electronic books